EGFR Mutation Positive Stage IV Non-Small-Cell Lung Cancer: Treatment Beyond Progression - Van Assche, Katrijn; Ferdinande, Liesbeth; Lievens, Yolande; Vandecasteele, Katrien; Surmont, Veerle (Frontiers in Oncology, 2014)
Non-small-cell lung cancer (NSCLC) is the leading cause of death from cancer for both men en women. Chemotherapy is the mainstay of treatment in advanced disease, but is only marginally effective. In about 30% of patients with advanced NSCLC in East Asia and in 10-15% in Western countries, EGFR mutations are found. In this population, first-line treatment with the tyrosine kinase inhibitors (TKI) erlotinib, gefitinib or afatinib is recommended. The treatment beyond progression is less well-defined. In this paper we present 3 patients, EGFR mutation positive, with local progression after an initial treatment with TKI. These patients were treated with local radiotherapy. TKI was temporarily stopped and restarted after radiotherapy. We give an overview of the literature and discuss the different treatment options in case of progression after TKI: TKI continuation with or without chemotherapy, TKI continuation with local therapy, alternative dosing or switch to next-generation TKI or combination therapy. There are different options for treatment beyond progression in EGFR mutation positive metastatic NSCLC, but the optimal strategy is still to be defined. Further research on this topic is ongoing.